PERANCANGAN BUKU FOTOGRAFI ESAI SEBAGAI MEDIA PROMOSI & INFORMASI DESTINASI BUDAYA BATU MEGALITIKUM DI KABUPATEN MANGGARAI TIMUR - Yung, Valeria Li; Pratama, Bintang Pramudya Putra; Nugroho, Didit Prasetyo (Ma Chung Press, Universitas Ma Chung, 2024)
East Manggarai Regency has great potential as a stunning cultural and natural tourist destination. One of the main attractions is the Megalithic Stone Site located in Watu Nggene Village. This site is an old cemetery located in the East Manggarai Region, Flores Island, Indonesia. However, initial observations show that there has been no significant effort from the government to effectively promote and disseminate information regarding this Megalithic Site. Therefore, a Photography Essay Book is needed that can help promote and inform this Megalithic Site to a wide audience. This research uses a qualitative method with descriptive analysis data analysis, so that the data collected will be analyzed and explained in detail in the form of descriptions. With this approach, a Photographic Essay Book entitled “Visit Megalithic Manggarai Timur,” which can provide information to prospective tourists both domestic and international, was created. The design concept of this book aims to visualize the beauty of culture, history, and natural scenery of East Manggarai realistically, accompanied by supporting narratives that explain each photo. This book measures 22 x 16 cm with a total of 100 pages, consisting of 75% full-color photos and 25% supporting narration. Supporting media includes social media instagram, posters, Bookmarks, Tote bags, tshirts,hat and tumblr that describe.